LES ROUTES RURALES ET INTERACTION RURALES-URBAINES EN PROVINCE DE LA TSHOPO (RDC) - Mbombo, ISSOMALAMBE; Longongo, Gabriel BOSANDJA; Mondenga, José LISUMBU; Bolimbo, Bernard LISENDJA (IJRDO - Journal of Social Science and Humanities Research, 2021)
The development of our entities is linked to that of infrastructure, particularly roads and schools, which are called upon to facilitate development as an essential pillar for economic growth. In the DRC as everywhere else, the interconnection between different environments effectively contributes to developments through the exchanges that take place there. Roads, as a catalyst for trade deserve regular maintenance because the scarcity and abundance of goods in these different environments are linked to them. The final objective pursued being to report on the place of city-countryside interactions in the province of Tshopo by road, to identify the consequences that these interactions have on the daily lives of populations.